GOVERNMANET PUBLIC RELATIONS IN FACING POLITICAL YEAR: TRAINING FOR LOCAL GOVERNMENT OF MAGETAN - Suteja, Rani Sukma Ayu; Rahayu, Titik Puji; Wahyudi, Irfan; Widodo, Suko; Septiani, Dina; Isnaini, Santi; Fitranisa, Intan; Puspa, Ratih (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The issues faced by Indonesia in the 2019 elections are likely to reemerge in the 2024 elections. In the 2019 elections, digital media became a highly effective tool for disseminating information related to politics and governance. Unfortunately, not all information available on digital media was accurate. Social media, in particular, saw a lot of misinformation and the spread of fake news (hoaxes). This led to a negative perception of the government among the public, which consequently influenced the opinions and political participation of Indonesian society. Therefore, a transformation is needed to support the formation of a positive government image. One of the strategies is maximizing government public relations. On August 8, 2023, the Communication Department at the Faculty of Social and Political Sciences, Universitas Airlangga, held a community service activity on the topic of government public relations training in Magetan Regency to address the political year. The main target of this activity was government officials in Bulukerto Subdistrict, Magetan District, Magetan Regency. The implementation mechanism consisted of three stages. In the initial stage, the community service team conducted surveys and coordinated with local government officials to gain a detailed understanding. During this stage, the Communication Department observed the involvement and performance of government public relations to obtain an initial overview of the strategies or designs used for the training. Subsequently, it was decided that the activity would be conducted through seminars and workshops covering topics such as public speaking, digital government, corporate social responsibility, and government public relations. After the activity, an evaluation was conducted to measure its success. It is hoped that this activity can serve as a foundation for improving the function of government public relations in addressing the political year and can be a supportive factor in ensuring the success of the 2024 elections.